Changes in the Monocytic Subsets CD14dimCD16+ and CD14++CD16− in Chronic Systolic Heart Failure Patients. (27th November 2012) - Amir, Offer; Spivak, Ilia; Lavi, Idit; Rahat, Michal Amit
Abstract : Different monocytic subsets are important in inflammation and tissue remodelling, but although heart failure (HF) is associated with local and systemic inflammation, their roles in HF are yet unknown. We recruited 59 chronic systolic HF patients (aged 58 ± 13 years, 45 males and 14 females) and 29 age-matched controls with no pervious heart disease. Compared to the controls, we found no change in the distribution of the CD14 + CD16 + monocytic subset, whereas the classical CD14 ++ CD16 − subset was decreased by 11% (P < 0.001 ), and the nonclassical CD14 dim CD16 + subset was expanded by 4% (P < 0.001 ) in HF patients and was inversely associated with severe HF (P = 0.015 ), as assessed by increased end-diastolic dimension (EDD). Compared to the control group, serum TNFα, IL-1β, IL-10, and IL-13 levels were significantly elevated in the HF patients. Specifically, IL-13 levels were positively correlated to the CD1CD14 dim CD16 + monocytic subset (r = 0.277, P = 0.017 ), and intracellular staining of IL-13 demonstrated that some of these monocytes produce the cytokine in HF patients, but not in the controls. We suggest that the inverse association between EDD values and the expansion of CD14 dim CD16 + monocytes that can produce IL-13 could be explained as a measure to counterbalance adverse remodelling, which is a central process in HF.